Analisis Keterkaitan Konsep Geografi Pada Muatan IPS di Kelas 3 Sekolah Dasar - Setyaningsih, Kristia (Pena Edukasia, 2024)
Social Sciences is a science that brings together selected concepts from various social sciences such as, history, economics, geography, sociology, anthropology, social psychology and political science. Social studies material taught since elementary school aims to prepare, develop, and shape students' skills to acquire the basic knowledge, attitudes, values, and skills needed for life in society. This study used a library research method, and used descriptive analysis. The results shows that social psychology basic concept dominated the teaching materials of social studies for lower grade classes.